TRANSFORMASI PARADIGMA KINERJA DAN KETAHANAN KEUANGAN PERUSAHAAN DALAM MENYIKAPI KRISIS: SUATU TINJAUAN SISTEMATIS TERHADAP STUDI EMPIRIS 2012–2022 - Nasution, Umar Hamdan (Bisnis-Net, 2024)
This study aims to conduct a systematic review of empirical research on corporate financial performance and resilience in responding to crises during the period 2012 to 2022. Using the PRISMA approach, 60 articles from reputable international (Scopus Q1–Q4) and national (Sinta 1–2) journals were analyzed based on thematic focus, methodology, and industrial sector. The findings indicate a paradigm shift from traditional ratio-based financial approaches to predictive models supported by digital technology and artificial intelligence. The study reveals that integrating historical financial data with unstructured information and applying machine learning algorithms enhances early warning systems for corporate financial distress. This review is expected to provide a conceptual foundation for developing a digital financial resilience model that supports strategic decision-making in the disruption era.